2007
DOI: 10.1086/509821
|View full text |Cite
|
Sign up to set email alerts
|

Stage‐Specific Adaptation of HypermutablePseudomonas aeruginosaIsolates during Chronic Pulmonary Infection in Patients with Cystic Fibrosis

Abstract: Mutator strains may evolve from the initially infecting PA strain and generate numerous variants with a loss of destructive virulence factors, probably because of selection for improved survival in the deteriorated CF lung but at the expense of the ability to live freely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
123
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 34 publications
6
123
0
Order By: Relevance
“…This study confirmed that non-mutator and mutator strains coexist in the respiratory tract for prolonged periods in advanced CF. The study also confirmed that mutator strains tend to be the predominant isolates in end-stage CF disease and show startling loss of virulence associated phenotypic traits, including reduced cytotoxicity, amino acid auxotrophy, and inability to survive in tap water (Hogardt et al, 2007). Therefore, the in situ development of isogenic strains appears to be a general phenomenon with mutations affecting the same set of genes, but the specific coding sequence alterations are independent events in clonally unique strains associated with the individual CF host.…”
Section: Accumulation Of Quorum Sensing Deficient Pa Reflects Developsupporting
confidence: 60%
See 4 more Smart Citations
“…This study confirmed that non-mutator and mutator strains coexist in the respiratory tract for prolonged periods in advanced CF. The study also confirmed that mutator strains tend to be the predominant isolates in end-stage CF disease and show startling loss of virulence associated phenotypic traits, including reduced cytotoxicity, amino acid auxotrophy, and inability to survive in tap water (Hogardt et al, 2007). Therefore, the in situ development of isogenic strains appears to be a general phenomenon with mutations affecting the same set of genes, but the specific coding sequence alterations are independent events in clonally unique strains associated with the individual CF host.…”
Section: Accumulation Of Quorum Sensing Deficient Pa Reflects Developsupporting
confidence: 60%
“…Longitudinal bacterial culture following patient disease progression suggests that a gradual decrease in bacterial diversity is associated with an increase in patient age and advanced pulmonary disease (Cox et al, 2010). Transmission of CF airway adapted strains, for example, a hyper-mucoid Pa, has never been reported (Aaron et al, 2004(Aaron et al, , 2010Feliziani et al, 2010;Furukawa et al, 2006;Hogardt et al, 2007;Oliver & Mena, 2010).…”
Section: Clinical Characteristics Of Pseudomonal Infection In the Airmentioning
confidence: 99%
See 3 more Smart Citations